Mengidentifikasi miskonsepsi matematika pada peserta didik sekolah dasar dengan speech delay - Napfiah, Siti; Kartika, Era Dewi; Setyaningsih, Sri Wahyu (International Journal of Progressive Mathematics Education, 2025)
Purpose: To analyze the mathematical concept comprehension of students with speech delay and investigate the correlation between communication impairments and mathematical cognition in elementary education. Design/methodology/approach: This descriptive qualitative study involved three second-grade students with speech delay. Data collection utilized mathematical concept understanding tests based on five indicators, supplemented by interviews and structured observations to ensure data depth and validity. Findings: Results indicate that the subjects' conceptual understanding is categorized as low, specifically regarding measurement and terminological accuracy. The findings demonstrate that restricted linguistic and communication abilities significantly hinder the internalisation of mathematical concepts. Practical implications: The study suggests that educators should integrate linguistic stimulation within inclusive mathematics instruction to support students with speech impediments in achieving optimal conceptual mastery. Originality/value: This research provides a unique contribution to mathematics education literature by uncovering the nexus between speech delay and mathematical conceptualisation, an area currently underexplored.   Purpose: Menganalisis kemampuan pemahaman konsep matematika peserta didik speech delay serta mengeksplorasi hubungan antara hambatan komunikasi dengan kognisi matematis di tingkat sekolah dasar. Design/methodology/approach: Penelitian kualitatif deskriptif ini melibatkan tiga siswa kelas 2 Sekolah Dasar yang mengalami speech delay. Instrumen pengumpulan data meliputi tes pemahaman konsep (berdasarkan lima indikator), wawancara, dan observasi terstruktur untuk memastikan kedalaman data. Findings: Pemahaman konsep matematika subjek berada pada kategori rendah, terutama pada materi ukuran dan akurasi penggunaan terminologi. Temuan menunjukkan bahwa keterbatasan kemampuan bahasa dan komunikasi secara signifikan menghambat proses internalisasi konsep matematis peserta didik. Practical implications: Studi ini merekomendasikan pendidik untuk mengintegrasikan stimulasi komunikasi ke dalam strategi pembelajaran matematika inklusif guna membantu siswa dengan hambatan bicara mencapai pemahaman konsep yang optimal. Originality/value: Memberikan kontribusi unik pada literatur pendidikan matematika dengan mengungkap keterkaitan antara hambatan perkembangan bahasa (speech delay) terhadap pemahaman konsep matematika yang masih jarang dieksplorasi.